Soil physical properties and their relationship with plasticity in a system under traditional tillage and no tillage - Hernández-Sánchez, Jazmín María de los Dolores; Figueroa-Sandoval, Benjamín; Martínez Menes, Mario R. (Revista Mexicana de Ciencias Agrícolas, 2019)
Tillage systems generate changes in soil properties, such as particle size distribution (DTP), structure and content of organic matter (MO), which in turn alters plasticity (limits of Atterberg), property that provides information on the mechanical behavior of the soil. The objective of this work was to evaluate the relationships between the Atterberg limits, the DTP and the MO content in a soil under traditional tillage (LT) and no tillage (NL). The samples were taken from the topsoil. For both plots the liquid limit (LL), plastic limit (LP), plasticity index (PI), MO content and DTP were determined. The NL presented a higher proportion of macroaggregates with respect to microaggregates compared to LT (89.16 and 85.59% respectively). There were no significant differences (p< 0.05) in the MO content between treatments, being higher for LT (4.2%) compared to NL (4.1%), as a result of which under the NL system there is a crop rotation that decreases the surface residue, while under LT the incorporation of crop residues is carried out. The LL and IP presented correlation with the clay content (0.6 and 0.4 respectively), but not for the MO content and contrary to what the literature indicates. It is concluded that the content of MO by itself, is not a sufficient indicator of the Atterberg Limits, for which it is recommended that for future investigations the degree of decomposition, quality and disposition of the MO with respect to the mineral particles of the soil matrix.
Keywords: Atterberg limits; organic matter; particle size distribution; tillage